Development of interactive learning assisted by x-mind to train high school students' conceptual understanding - Elta Puja Candera; Rosane Medriati; Eko Risdianto (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
This study aims to develop a product in the form of an interactive concept map assisted by learning media, namely the X-mind application to train students' conceptual understanding. The method used is research and development (Rnd) which has 5 ADDIE stages there are Analysis, Design, Development Implementation and Evaluation which includes material expert tests and media expert tests. The results of the percentage that has been given by material validation experts is 96.05% and the results given by media validation experts are 96%, thus it can be concluded that interactive learning through concept maps assisted by the X-mind application is very feasible in learning physics material elasticity with an average result expert validation test of 96.02% is very feasible to develop. Then to strengthen this product development, data collection on student perceptions of the products that have been developed was carried out with the results of the presentation aspect 86.8%, understanding aspect 86.6%, interest aspect 85.2% and attention aspect 86.6% with an average percentage of 86.3% is very good to use.